THE SPORT LIKE SOCIAL PRACTICE: REFLECTIONS AND CONTRIBIÇÕIS OF THE SCHOOL SÔNIA HENRIQUES BARRETO FOR THE SYSTEM OF PUBLIC EDUCATION IN THE MUNICIPALITY OF LARANJAL OF THE JARI/AP (Fiep Bulletin - online, 2019)
This article has the aim to reflect on the value of the sport in the school field and the use of east like an important toolwhile practical pedagogical, from the experiences of the selection of futsal of the Provincial School Sônia Henriques Barreto,located in the Municipality of Laranjal of the Jari/Amapá. The investigation presents like a continuous work that visa accompanythe work developed in this institution of education, In the perspective to boost the sport like social practice in the pubic schoolsamapaenses, motivating increasingly professors and students to incentivar this modality. The importance of the work is in doingreflections and contributions on the use of the sport like able pedagogical tool to teach further of the ginásios sportive, In themeasure in that it discerns a committed physical education with the social reality of the subjects, able to promote a physicaleducation pupil of quality in the public net amapaense. The methodology consisted in a qualitative investigation, through a studioof case, with twenty students of the fundamental education in the School Sônia Henriques Barreto and four professors of theeffective picture of physical education, That form part of the net of provincial education amapaense. The recolección of data usedwas the technician of the participatory observation of the coachings, meetings with the parents of the students, classes ofphysical education, games in municipal tournaments, provincial and regional that became during the period that the studentswere taking part of the School Games in 2018, as well as interview semiestruturada with professors and students. For theembasamento theoretical buscou-if articles, seen again, photos and videos of the championships that could esclarecer andprovide new horizons in the process of education-learning in physical education.
Keywords: Sport; pedagogical Practice; social Practice